Determinants of clinic doctors' attitudes concerning antimicrobial prescription for patients with common colds or bronchitis: Additional analysis of a nationwide survey conducted by the Japanese Society of Chemotherapy and the Japanese Association for Infectious Diseases. Issue 2 (February 2021) - Morioka, Shinichiro; Gu, Yoshiaki; Tsuzuki, Shinya; Fujitomo, Yumiko; Soeda, Hiroshi; Nakahama, Chikara; Hasegawa, Naoki; Maesaki, Shigefumi; Maeda, Masayuki; Matsumoto, Tetsuya; Miyairi, Isao; Ohmagari, Norio
Abstract: Background: In 2019, the Japanese Society of Chemotherapy and the Japanese Association for Infectious Diseases reported nationwide, cross-sectional questionnaire survey data investigating the clinical status of clinic doctors' attitudes to antimicrobial stewardship. This study aimed to identify factors determining clinic doctors' attitudes concerning antimicrobial prescription for patients with a common cold or bronchitis. Methods: In February 2018, 1500 randomly selected community-based medical clinics in Japan were sent a questionnaire. Primary and secondary endpoints were clinic doctors' attitudes concerning antimicrobial prescription, and antimicrobial medication types prescribed for patients with a common cold or bronchitis, respectively. We used multivariable linear regression analysis to identify factors associated with primary and secondary outcomes. Results: We analyzed 269 of 274 responses (response rate, 18.3%). Linear regression analysis was used to identify determinants of proactive attitudes to antimicrobial prescription, including whether clinic doctors encountering patients with upper respiratory symptoms and no underlying illnesses, and diagnosed with a common cold would prescribe antimicrobial medication (β = 0.283, t = 4.279, p  = 0.000); whether clinic doctors frequently experienced requests from patients (or their families) with a common cold to prescribe antimicrobial medication (β = 0.389, t = 6.133, p  = 0.000), and; clinic doctors' awareness of antimicrobial stewardship in the past year (β = −0.157, t = −2.456, p  = 0.015). Determinants of proactive attitudes to prescribing broader-spectrum antimicrobials for patients with a common cold included clinic doctors' attitudes concerning antimicrobial prescription (β = 0.165, t = 2.622, p  = 0.009), whether the respondent was a pediatrician (β = −0.288, t = −4.583, p  = 0.000), and clinic doctors' attitudes to antimicrobial prescription (β = 0.262, t = 4.075, p  = 0.000) for patients with bronchitis. Conclusion: This study identified factors among clinic doctors that determined their attitudes to antimicrobial prescription concerning patients with a common cold or bronchitis. Identification and targeting of clinic doctors who unnecessarily prescribe antimicrobial medication is urgently required to promote antimicrobial stewardship in an outpatient setting.